Gregor and the curse of the warmbloods - Collins, Suzanne (Collins, Suzanne. Underland chronicles, 2005)
Eleven-year-old Gregor and his younger sister, Boots, return to the Underworld beneath New York City to find the cure for a terrible plague that threatens the life of their mother, as well as the lives of the people, bats, and rats who populate the underworld.